Newborn Screening for Thyroid-stimulating Hormone as an Indicator for Assessment of Iodine Status in the Republic of Macedonia - Anastasovska Violeta; Kocova Mirjana (Society of Medical Biochemists of Serbia, 2016)
Iodine deficiency is associated with goiter and impaired brain function leading to cretinism. An increased frequency of thyroid-stimulating hormone (TSH) measurements above 5 mlU/L on newborn screening points toward an impaired iodine status of the population.